Invasive cutaneous Neoscytalidium infections in renal transplant recipients: a series of five cases. Issue 1 (December 2015) - Garinet, Simon; Tourret, Jérôme; Barete, Stéphane; Arzouk, Nadia; Meyer, Isabelle; Frances, Camille; Datry, Annick; Mazier, Dominique; Barrou, Benoit; Fekkar, Arnaud
Abstract Background Neoscytalidium species (formerlyScytalidium species ) are black fungi that usually cause cutaneous infections mimicking dermatophytes lesions. Very few publications have reported invasive or disseminated infections. Case presentation In this paper, we report the clinical presentations, treatments and outcomes of five cases of invasiveNeoscytalidium infections with cutaneous involvement, including two cases with disseminated infection, in five renal transplant recipients. To our knowledge, this is the first report of a series—albeit small—of renal transplant patients in whom this infection was identified. All cases occurred in a single hospital in Paris, France, between 2001 and 2011. Patients all originate from tropical area. Conclusion Treatments ofNeoscytalidium infection varied greatly, underlining the lack of a recommendation for a standardized treatment. All patients were cured after long-term antifungal therapy and/or surgical excision. Interestingly, one patient with disseminated infection involving the left elbow, the right leg, the lungs and the nasal septum was cured by medical therapy only without surgery. This may suggest that in contrast to others mycoses (such as mucormycosis), an adequate medical treatment could be sufficient for treatingNeoscytalidium . We also point out the difficulties we had in diagnosing two patients with Kaposi's sarcoma because of the similarity of the lesions. Furthermore, our report underlines the need to check for this rare infection in immunocompromised kidney transplant recipients originating from tropical areas.